Lernpfade von extrinsisch und intrinsisch motivierten Fachsprachenlernenden im Selbstlernkurs LSP-TEOC.Pro - Nause, Nicolas; Woźniak, Joanna (Glottodidactica, 2025)
The paper examines differences and similarities among learners regarding their approaches to the LSP-TEOC.Pro self-study course designed for enhancing competences in LSP teacher training. The inquiry addresses differences and similarities between extrinsically and intrinsically motivated course participants, and explores how forthcoming participants could benefit from these insights. Within this discussion, an already existing typology is continued, with a qualitative approach which analyses, interprets and explains the quantitative results in depth, specifically, the two identified groups of learners distinguished by their extrinsic or intrinsic motivation. The discussion reveals differences in approaches between the two groups, and findings suggest that these differences manifest across three levels: 1. time actively spent in the system, 2. activities completed, including optional materials and tests, and 3. the sequence in which modules are completed.